Hanseníase, risco e vulnerabilidade: perspectiva espaço-temporal e operacional de controle no estado da Bahia, Brasil - Souza, Eliana Amorim de (2017)
Leprosy control remains as a great and complex challenge over time and space in Brazil. In areas of higher risk, the disease presents a focal nature of occurrence and Bahia is a state with high endemicity clusters of the disease. There is a need for deepening epidemiological and operational questions in the perspective of time and space. In this sense, this study characterizes the epidemiological and operational patterns of leprosy, as well as factors associated with its spatio-temporal distribution in the State of Bahia. This is a population-based ecological study of spatial-temporal series using official morbidity and mortality data on leprosy. The state's 417 municipalities and its nine health regions were used as the geographical units of analysis. The morbidity database encompassed all new cases of residents in the state diagnosed between 2001-2014 and all deaths that had leprosy as a multiple cause in the period 1999-2014 were analyzed. The work was structured in four stages that comprised the methodological paths adopted. The first part describes the epidemiological and operational indicators of leprosy control, as well as the time trend analysis using joinpoint regression. Then, it characterizes spatial patterns and spatial-temporal clusters of risk for detection, recent transmission and late diagnosis by the analysis of spatial dependence - the Local Moran and Getis-Ord indices and the recognition of clusters. The third part characterizes the spatial-temporal patterns, and clusters of high spatio-temporal risk for mortality related to leprosy, in addition potentially associated factors. Finally, on the last stage there is the recognition of the social and programmatic dimensions of the vulnerability for the occurrence of leprosy and the integrated analysis of potential determinants and social constraints to the different patterns of spatial and temporal distribution of morbidity and mortality of the disease. A total of 40,054 cases of the disease were reported in 14 years, with a coefficient of detection of 20.41/100,000 inhabitants, 5.83/100,000 inhabitants for children and 5.7/100,000 for grade 2 of physical disability (G2PD) at the diagnosis of every 100,000 inhabitants. Over 16 years, leprosy was recorded for 481 deaths (proportional mortality: 0.04%; 95% CI: 0.004-0.05), 188 (39.1%) as principal cause of death and 293 (60.9%) as an associated cause. The average annual number of deaths was 30 deaths per year (95% CI: 23.4-36.7), with average annual coefficient of 0.21 deaths/100,000 inhabitants (95% CI: 0.13-0.29). The coefficient of detection of new cases was significantly higher among those ≥70 years of age (RR: 8.45; 95% CI: 7.08-10.09), black people (RR: 1.38; 95% CI: 1.33-1.43), residents in medium-sized city (RR: 2.80; 95% CI: 2.50-3.13) and residence outside the state capital (RR: 1.72; 95% CI: 1.54-1.92). The detection of new cases with G2PD at diagnosis was significantly greater among men (RR: 2.4; 95% CI: 1.6-3.4). There was a trend of reduction in coefficient of general detection (Average Annual Percent Change [AAPC] -0.4; 95% CI: 2.8 to 1.9), maintenance in children (AAPC 0.2; 95% CI: -3.9 to 4.5), in addition to the increase for cases with G2PD at diagnosis (AAPC 4.0; 95% CI: 1.3 to 6.8) and with multibacillary classification (AAPC 2.2; 95% CI: 0.1 to 4.3). The major Clusters identified in the North, West, and Extreme-South regions of Bahia State held high rates sustained over time. Almost half of the contacts recorded was not examined, while the proportion of cure in the cohort was 85.0%, the treatment dropout of 5.5% and a relapse of 3.8%. There was a significant trend of increase of contacts investigated and reduction of treatment dropout, so more expressive trend among women. Spatial analysis shows a large number of cities with poor performance of operational indicators, including the North and Extreme-South regions. There is large number of cities with poor or regular performance of health services to assess the degree of physical incapacity at the time of diagnosis. The evaluation of the indicator of G2PD shows low or media effectiveness of activities of timely detection in a significant number of cities in Bahia. In addition to reveal possible hidden endemics. The 25 cities that constitute the main Clusters show social, demographic, economic, indicators of access and quality of health services that point to different dimensions of social and programmatic vulnerability. The main Clusters identified in the North and Extreme-South regions of the State hold cities with high vulnerability. The deaths related to leprosy are associated with complications of leprosy reactions and adverse effects of therapy. In conclusion, the leprosy remains a public health problem in the State of Bahia over 16 years and might remain so for decades, in view of the fragility of control actions. High endemicity, active transmission, late diagnosis, likely hidden endemics and death related to leprosy compose this context. Evidences of unequal patterns of morbidity and mortality in both space and time along with the recognition of overlapping Clusters of different indicators reinforce the existence of priority areas. The fight against leprosy in the State passes through the expansion of coverage and qualification of control actions, rather the approach of contacts. The integration of elements of vulnerability to the agendas of confrontation for overcoming the social determinants of disease must be one of the major focus of the control programs.